Heatwave and its effect on productivity in India - Heng, Nicole En-Hui (Nanyang Technological University, 2023)
Concentrations of global greenhouse gases (GHG) and the closely relevant Earth’s temperature have been on the rise over the years. This study attempts to study the degree of heatwave impact on workers’ productivity. The effects of sex, age, education level, household size, job status, and occupation as control variables were also explored. Heatwaves were revealed to have negative and significant effects on workers’ productivity. The results alert policymakers and business owners of the devastating economic impact of heatwaves and prompts them to introduce climate-controlled conditions at workplaces.